(untitled) - Hill, John W. (Upper Saddle River, New Jersey, 1996)
This book retains the relaxed, easy-to-read style of the previous edition to provide integrated coverage of organic and biochemistry, applications, and tools that foster problem-solving skills. More than any other, this text offers balance-in the topics presented, and in its presentation of the subject of chemistry. The authors focus on three mains areas to help readers master the core concepts of general chemistry and enhance their problem-solving skills: problem-solving support and active assessment, conceptual development, and visualization of the molecular behavior of matter. For anyone who wants a relaxed, easy-to-read book that emphasizes major topics in chemistry as well as problem-solving techniques.
Keywords: Chemistry